A history of Christian conversion - Kling, David W. (Oxford University Press, 2020)
"Conversion has played a central role in the history of Christianity. In this first in-depth and wide-ranging narrative history, David W. Kling examines the dynamic of individuals, families, and people groups who turn to the Christian faith. Global in reach, this book progresses from early Christian beginnings in the Roman world to Christianity's expansion into Europe, the Americas, China, India, and Africa. Although conversion is often associated with a particular strand of modern Christianity (evangelical) and a particular type of experience (sudden, overwhelming), it is, when examined over two millennia, a phenomenon far more complex than any one-dimensional profile would suggest. No single, unitary paradigm defines conversion, and no easily demonstrable process accounts for why people convert to Christianity. Rather, a multiplicity of factors-historical, personal, social, geographical, theological, psychological, and cultural-shape the converting process. A History of Christian Conversion not only narrates the conversions of select individuals and peoples. It also engages current theories and models to explain conversion and examines recurring themes in the converting process: gender, agency, motivation, testimony, coercion, self-identity, "true" conversion, music, communication, the body, and divine presence. Accessible to scholars, students, and those with a general interest in conversion, Kling's book is, to date, the most satisfying and comprehensive account of conversion in Christian history; this major work will become a standard must-read in conversion studies"--